Rust inhibition mechanism of reinforced concrete by alcohol-amine corrosion inhibitor under the coupling of composite salt erosion, freeze-thaw cycle and dry-wet cycle - Jiaqi Liu; Meiyan Hang; Minghui Jiang; Hongbin Song (Case Studies in Construction Materials)
The purpose of this study is to propose an efficient and convenient alcohol-amine corrosion inhibitor (ACI) to enhance the durability of reinforced concrete in hostile environments. In this study, reinforced concrete without ACI and with 0.5 %, 1.0 %, and 1.5 % ACI, respectively, were placed into a 10 % composite salt solution for coupling test of freeze-thaw cycle and dry-wet cycle. The rust resistance and CSE-FDC resistance of ACI were studied by macroscopic tests (electrochemical impedance spectroscopy (EIS) and dynamic electrode potential curve (DPP), mechanical properties and mass loss), and the influence of ACI on the pore structure of reinforced concrete and the micro-morphology of steel surface was studied by microscopic tests (pore spacing parameters, electron microscope scanning (SEM) and X-ray energy spectrum (EDS)).The findings revealed that the CSE-FDC resistance of reinforced concrete with 0.5 %, 1.0 % and 1.5 % ACI increased by 51.62 %, 66.73 % and 32.82 %, respectively, and the porosity decreased by 50.10 %, 69.10 %, and 23.57 %, respectively, compared with reference specimens. ACI can significantly delay the depassivation of steel by harmful ions and improve the electrochemical properties of steel. When ACI was doped at 1.0 %, the Rp of the steel reached a peak value of 1034.00 Ω·cm2, which was in a low corrosion state, and the rust inhibition efficiency reached a maximum value of 98.05 %. ACI was mainly adsorbed on the steel surface by the physicochemical interaction of N atoms and -OH to increase the passivation film resistance, thus increasing the chloride ion threshold and passivation film stability to enhance the corrosion resistance of steel. The application of this research not only offers a new method for inhibiting the corrosion of steel in concrete but also offers theoretical knowledge and technical support for further study on the corrosion resistance of steel under a harsh environment.